Human movement detection and classification capabilities using passive Wi-Fi based radar - Razali, Hidayatusherlina; Abd Rashid, Nur Emileen; Nasarudin, Muhammad Nazrin Farhan; Ismail, Nor Najwa; Ismail Khan, Zuhani; Enche Ab Rahim, Siti Amalina; Megat Ali, Megat Syahirul Amin; Zakaria, Nor Ayu Zalina (International Journal of Electrical and Computer Engineering (IJECE), 2024)
Human detection and classification via Wi-Fi transmission have received a lot of attention in recent years as crucial facilitators in security and human-computer interaction (HCI). The passive Wi-Fi radar (PWR) system used by previous researchers applied cross-ambiguity function (CAF) and CLEAN algorithms to process the detected signals. This paper explores the feasibility and viability of a PWR system in detecting and classifying human movements without utilizing CAF and CLEAN algorithms. The movements are performed by four participants but with comparable body sizes and heights. Three daily human movements are investigated namely walking, bending, and sitting, with each participant performing each movement 24 times, providing a total of 96 samples per activity. The system is evaluated based on the consistency of the signal pattern in a frequency domain and the percentage accuracy is assessed using an artificial neural network (ANN) classifier and trained using a leave-one-out cross-validation (LOOCV) method. The frequency domain results reveal that the signals are consistent, with no noticeable variations or changes in the voltage intensity or shape of the main lobe. The classification of the movements shows that the classifier has an overall accuracy of 97.6%.